2020
DOI: 10.1038/s41438-020-00342-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide SNP discovery and core marker sets for assessment of genetic variations in cultivated pumpkin (Cucurbita spp.)

Abstract: Three pumpkin species Cucurbita maxima, C. moschata, and C. pepo are commonly cultivated worldwide. To identify genome-wide SNPs in these cultivated pumpkin species, we collected 48 F 1 cultivars consisting of 40 intraspecific hybrids (15 C. maxima, 18 C. moschata, and 7 C. pepo) and 8 interspecific hybrids (C. maxima x C. moschata). Genotyping by sequencing identified a total of 37,869 confident SNPs in this collection. These SNPs were filtered to generate a subset of 400 SNPs based on polymorphism and genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
(57 reference statements)
2
15
0
1
Order By: Relevance
“…We also found that the 75 cultivars were distinguished completely when the 43rd SNPs were added, indicating that the discriminatory power of the core SNPs increased along with the number of SNPs used. This phenomenon was also found in pumpkin, where the 96, 48, 24, and 12 core SNP sets were able to identify 85.2%, 63.2%, 24.2%, and 4.9% of the 223 pumpkin accessions, respectively (Nguyen et al, 2020), again indicating a positive correlation between the germplasm discrimination power and the core SNP number. For each cultivar, the genotypes of the 50 core SNPs can be used for their unique DNA fingerprint or applied for rapid seed purity tests.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…We also found that the 75 cultivars were distinguished completely when the 43rd SNPs were added, indicating that the discriminatory power of the core SNPs increased along with the number of SNPs used. This phenomenon was also found in pumpkin, where the 96, 48, 24, and 12 core SNP sets were able to identify 85.2%, 63.2%, 24.2%, and 4.9% of the 223 pumpkin accessions, respectively (Nguyen et al, 2020), again indicating a positive correlation between the germplasm discrimination power and the core SNP number. For each cultivar, the genotypes of the 50 core SNPs can be used for their unique DNA fingerprint or applied for rapid seed purity tests.…”
Section: Resultsmentioning
confidence: 68%
“…However, there is a large gap between the development of SNP markers and their application in practical breeding processes because SNP genotyping requires complex detection technologies and has high costs. Recently, multiple cost‐effective and flexible core SNP sets based on the KASP technology have been developed in rice, Brassica rapa , pepper and pumpkin (Du et al, 2019; Li et al, 2019; Nguyen et al, 2020; Yang et al, 2019). With high representation and resolution, core SNP sets have been widely used in genetic diversity analysis, marker‐assisted selection, and seed intellectual rights protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classical markers are less preferred by breeders because they are less polymorphic and are highly influenced by the environment as well as influenced by the plant growth stage [4]. Molecular markers such as single-nucleotide polymorphism (SNP) markers are the most ideal to use in markerfacilitated breeding because they are codominant, uniformly distributed throughout the genome, highly reproducible, and highly polymorphic [6]. The genome-wide association study (GWAS) is a modern technique used to detect connotation between genetic variants and traits in samples from populations mainly based on SNP markers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers including random amplified polymorphic DNA (RAPD), amplified fragment length polymorphism (AFLP), simple sequence repeat (SSR), and single-nucleotide polymorphism (SNP) have been developed to construct genetic linkage map in Cucurbita [ 33 , 34 , 35 ]. Improvements of whole genome sequences and high-density genetic maps have promoted the precision of genomic data in Cucurbita and support a better foundation for the research and application of candidate genes in Cucurbita species [ 36 , 37 , 38 , 39 , 40 , 41 ]. With effective utilization of molecular markers and genetic map resources, QTLs for many agronomic traits and candidate genes have been identified and applicated accordingly in breeding selection [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%